Comparativo de cuatro tipos de fertilizantes foliares inorgánicos y su efecto sobre el crecimiento en vivero de Moringa oleifera Lam “moringa” en Zungarococha, Perú – 2020 - Sicard Reategui, Jessica Marina (2024)
The production of quality seedlings of Moringa oleifera Lam “MORINGA” to produce forage of high nutritional quality for animal feeding is a necessity that must be carried out research work and the faculty of agronomy presents the research titled: COMPARATIVE OF FOUR TYPES OF FERTILIZERS INORGANIC FOLIARS AND THEIR EFFECT ON THE NURSERY GROWTH OF Moringa oleifera Lam “MORINGA” IN ZUNGAROCOCHA, PERU – 2020. With a Complete Random Design with five treatments and four repetitions, the treatments under study were: T0 (Control), T1 (More leaves 20-20-20), T2 (Super foliage 45-10-10), T3 (Pawer leaves 40-10-10) and T4 (Extra foliage 36-6-10). The results obtained were the following: For plant height, T2 (Super foliage 45-10-10) occupied the first places with 82.63 centimeters. Treatment T2 (Super foliage 45-10-10) obtained the best results with 39.13 grams in aerial biomass. Regarding basal diameter, treatment T2 (Super foliage 45-10-10) achieved 9.45 millimeters. In root length, treatment T1 (More leaves 20-20 20) obtained first place with 13.23 centimeters. Regarding the number of leaves per plant, the T2 treatments (Super foliage 45-10-10) with 12.2 leaves.